Reactive Uptake of Sulfur Dioxide and Ozone on Volcanic Glass and Ash at Ambient Temperature. Issue 18 (18th September 2017) - Maters, Elena C.; Delmelle, Pierre; Rossi, Michel J.; Ayris, Paul M.
Abstract: The atmospheric impacts of volcanic ash from explosive eruptions are rarely considered alongside those of volcanogenic gases/aerosols. While airborne particles provide solid surfaces for chemical reactions with trace gases in the atmosphere, the reactivity of airborne ash has seldom been investigated. Here we determine the total uptake capacity (Ni M ) and initial uptake coefficient ( γ M ) for sulfur dioxide (SO2 ) and ozone (O3 ) on a compositional array of volcanic ash and glass powders at ~25°C in a Knudsen flow reactor. The measured ranges of Ni SO2 and γ SO2 (10 11 –10 13  molecules cm −2 and 10 −3 –10 −2 ) and Ni O3 and γ O3 (10 12 –10 13  molecules cm −2 and 10 −3 –10 −2 ) are comparable to values reported for mineral dust. Differences in ash and glass reactivity toward SO2 and O3 may relate to varying abundances of, respectively, basic and reducing sites on these materials. The typically lower SO2 and O3 uptake on ash compared to glass likely results from prior exposure of ash surfaces to acidic and oxidizing conditions within the volcanic eruption plume/cloud. While sequential uptake experiments overall suggest that these gases do not compete for reactive surface sites, SO2 uptake forming adsorbed S(IV) species may enhance the capacity for subsequent O3 uptake via redox reaction forming adsorbed S(VI) species. Our findings imply that ash emissions may represent a hitherto neglected sink for atmospheric SO2 and O3 . Key Points: Sulfur dioxide and ozone are taken up on volcanic glass/ash at ambient temperature likely at basic and reducing surface sites, respectively A typically lower ash reactivity toward these gases may reflect exposure to acidic and oxidizing conditions in the volcanic plume/cloud Measured uptake capacity and coefficient values suggest that ash emissions may represent a sink for atmospheric sulfur dioxide and ozone